Поняття та етапи інституціоналізації політичних партій в Україні - Петришина-Дюг, Г.Г. (Держава і право, 2011)
Досліджується поняття та сутність інституціоналізації політичних партій. Розглядаються етапи інституціоналізації політичних партій в Україні. Исследуется понятие и сущность институционализации политических партий. Рассматриваются этапы институционализации политических партий в Украине. In this article the concept and nature of the institutionalization of political parties studied, different points of view of researchers outlined the problems considered. Stages of the institutionalization of political parties in Ukraine is considered separately and analyzed.